COMPARISON OF HEPATITIS C ANTIBODY ASSAYS AND EVALUATION OF AGREEMENT BETWEEN HEPATITIS C ANTIGEN AND PCR RESULTS - Iqbal, Sahar; Baig, Samina; Naseem, Saima; Naeem, Syed Talha; Fatima, Ambreen; Khan, Saeed (Journal of Ayub Medical College Abbottabad, 2022)
Background: Hepatitis C is associated with a wide range of health repercussions. Pakistan is one of the highly prevalent countries of Hepatitis C Virus (HCV) infection. The availability of cost-effective, robust, and reliable screening and diagnostic tests for hepatitis C is important to address the disease burden. Standardization of screening and diagnostic assays in clinical laboratories is crucial for achieving big goals. Objectives of this study are to correlate the results of two different HCV antibody (HCV Ab) assays and to examine the correlation of HCV core antigen (HCV c Ag) results with HCV PCR for HCV infection diagnosis. Methods: This descriptive cross-sectional study was carried out from November to December 2020 at Dow University of Health Sciences. Total number of 40 HCV Ab samples were analysed by both chemiluminescence (CMIA) and electrochemiluminescence (ECLIA) immunoassays. Tests for HCV RNA PCR and HCV c Ag were performed on all samples. Results of screening and diagnostic assays were correlated and agreements were examined. Statistical analysis for agreement was carried out by using R software version 3.6.3 through AC1 Gwetz Statistic. The study was approved by the institutional ethical review committee. Results: An agreement of 0.73 and 0.95 was found between two different HCV Ab immunoassays and HCV c Ag and HCV PCR, respectively. Conclusion: We found a good correlation between CMIA and ECLIA for HCV Ab. An excellent correlation was found between HCV c Ag and HCV PCR. Based on our study findings, HCV c Ag is a candidate test for the diagnosis of active HCV infection.